2010
DOI: 10.3855/jidc.680
|View full text |Cite
|
Sign up to set email alerts
|

Tungiasis infestation in Tanzania

Abstract: Tungiasis is caused by the jigger flea Tunga penetrans. We describe a case of severe infestation from Kigoma region, Western Tanzania. A 19-year-old male with epilepsy and mental disability presented with ulcerated and inflamed toes. Clinical examination revealed the presence of approximately 810 embedded jigger fleas on the feet, and another 60 lesions on the hands. The patient presented with fissures on the feet, hands and soles. He had difficulty walking and erythematous, oedematous, ulcerated and inflamed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Tungiasis associated morbidity, such as pain, difficulty in walking and deformity of toenails, was commonly reported (Table 2). These clinical manifestations have been reported in different studies [8,10,13,14]. One of the most common symptoms reported in our study was itching (62.9% of patients), which is believed to facilitate the leakage of eggs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Tungiasis associated morbidity, such as pain, difficulty in walking and deformity of toenails, was commonly reported (Table 2). These clinical manifestations have been reported in different studies [8,10,13,14]. One of the most common symptoms reported in our study was itching (62.9% of patients), which is believed to facilitate the leakage of eggs.…”
Section: Discussionsupporting
confidence: 77%
“…Similar data were recorded in 1984 among primary and post-primary school pupils in the Niger delta [5]. Knowledge on the current epidemiological situation of tungiasis in Eastern Africa is limited: to our knowledge, only two studies have been carried out in the Northwestern area of Tanzania [10,11]; both studies confirmed that prevalence and morbidity are high.…”
Section: Introductionsupporting
confidence: 75%
“…4 Here we present the clinical findings, demographic and environment characteristics of five individuals identified during a cross-sectional study in Kasulu district, western Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…[5], in deprived communities with poor housing standards, social neglect, and insufficient health-seeking behavior, tungiasis has a high transmission potential and increased likelihood for severe disease [5]. A severe form of tungiasis may manifest with digit deformation, chronic lymphedema, sepsis, and tetanus [6]. Our case had severe digit deformation and septicemia.…”
Section: Discussionmentioning
confidence: 95%